1996
DOI: 10.1097/00000539-199603000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Anesthesia Based on Large Versus Small Doses of Fentanyl on Natural Killer Cell Cytotoxicity in the Perioperative Period

Abstract: Surgical stress and general anesthesia suppress immune functions, including natural killer cell cytotoxicity (NKCC). This suppression could be attributable, at least in part, to opiates. We have previously shown that large-dose fentanyl administration suppressed NKCC in rats. The present study sought to compare the effects of two anesthetic protocols, based on large- (LDFA) versus small (SDFA)-dose fentanyl anesthesia on NKCC in the perioperative period. Forty patients were included in this study; half were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
67
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(72 citation statements)
references
References 18 publications
1
67
1
3
Order By: Relevance
“…Acute and chronic administration of exogenous opioids including the one most commonly used-morphine -inhibits components of the cellular and humoral immune function such as antibody production, NK cell activity, cytokine expression, blood lymphocyte proliferative responses to mitogen, and phagocytic activity [32][33][34][35]. While many studies have tested the immunosuppressive effects of morphine in vitro and in vivo in rodents and humans [32,33,35,36], other opioids have been shown to also possess immunosuppressive effects, e.g., therapeutic agents such as fentanyl [37][38][39], or pharmacological tools such as subtype-specific opioid receptor agonists U50 488H, deltorphin II, or DPDPE [40].…”
Section: Opioids Are Immunosuppressivementioning
confidence: 99%
“…Acute and chronic administration of exogenous opioids including the one most commonly used-morphine -inhibits components of the cellular and humoral immune function such as antibody production, NK cell activity, cytokine expression, blood lymphocyte proliferative responses to mitogen, and phagocytic activity [32][33][34][35]. While many studies have tested the immunosuppressive effects of morphine in vitro and in vivo in rodents and humans [32,33,35,36], other opioids have been shown to also possess immunosuppressive effects, e.g., therapeutic agents such as fentanyl [37][38][39], or pharmacological tools such as subtype-specific opioid receptor agonists U50 488H, deltorphin II, or DPDPE [40].…”
Section: Opioids Are Immunosuppressivementioning
confidence: 99%
“…Unfortunately, it also has been established that opioids (morphine in particular) inhibit cellular and humoral immune function in humans. [35][36][37] There are no data directly implicating opioids in cancer genesis in humans, but animal data strongly suggest that they may contribute to cancer recurrence in the clinical setting. For example, in rodent studies, it was demonstrated that morphine is proangiogenic and promotes breast tumor growth.…”
Section: Opioidsmentioning
confidence: 99%
“…Opioids inhibit cellular and humoral immune function in humans 36 Morphine inhibits spontaneous and cytokine-enhanced NK cell cytotoxicity [35][36][37] In contrast, IV fentanyl increases NK cell cytotoxicity and circulating CD16(ϩ) lymphocytes in humans 41 Opioid-induced promotion and stimulation of angiogenesis 39 ␤-adrenergic blockade ␤-blocker (nadolol) and a prostaglandin synthesis inhibitor (indomethacin) attenuated the metastasis-promoting effects of surgery when used alone or in combination 11 …”
Section: Opioidsmentioning
confidence: 99%
“…1 Pain also suppresses natural killer cell activity by decreasing cytotoxic T cells and reduction of neutrophil phagocytic activity, resulting in critical impairment of the immune system. 1,7,8 All of these physiologic factors can lead to worsening of patient condition, increase in complications, and prolonged length of stay for the patient.…”
mentioning
confidence: 99%